Digital Transformation in Postal Logistics: A Design Science Approach to Enhancing Operational Performance through Geocoding and Voice-Assisted Sorting Systems - Meilia Risna; Pertiwi Utami; Umi Khulsum; Nur Azizah Zuhriyah; Tulus Suryanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Despite ongoing digital transformation in logistics, conventional postal sorting systems remain vulnerable to routing errors and operational inefficiencies, implying the need for more intelligent sorting solutions. This study aims to develop a web-based logistics sorting system integrating barcode scanning, geocoding automation, and voice-assisted technology to enhance operational performance in the Jakarta Premier Main Branch Office of Pos Indonesia. Employing a Design Science Research (DSR) approach, the study involved four stages: problem identification, system design, pilot implementation, and performance evaluation. The developed system was tested through a three-week pilot project using operational performance indicators, including sorting accuracy, processing time, and Service Level Agreement (SLA) compliance. The findings demonstrate that the proposed system substantially improved sorting accuracy from 86.5% to 96.7%, reduced average processing time by approximately 35%, and enhanced SLA compliance through more accurate delivery zone classification and real-time operational support. The voice-assisted interface also reduced operators’ cognitive workload and improved workplace efficiency. These findings emphasize the strategic role of digital logistics technologies in strengthening operational excellence and service quality, providing practical insights for postal organizations seeking sustainable digital transformation and intelligent logistics management.